Analysis of independent risk factors for progression of different degrees of diabetic retinopathy as well as non-diabetic retinopathy among type 2 diabetic patients - Li, Zheng; Tong, Jie; Liu, Chang; Zhu, Mingqiong; Tan, Jia; Kuang, Guoping (Frontiers in Neuroscience, 2023)
Purpose: To study the independent risk factors for progression of different degrees of diabetic retinopathy (DR) as well as non-DR (NDR) among type 2 diabetic patients. Methods: This cross-sectional study included 218 patients with type 2 diabetes between January 2022 and June 2022. All the patients were divided into two groups: the DR group and the NDR group. The DR group was subdivided into the mild, moderate and severe non-proliferative DR (NPDR) group and the proliferative DR (PDR) group. Data recorded for all patients included age, gender, duration of diabetes, blood pressure, glycated hemoglobin (HbA1c), fasting blood glucose (FBG), blood lipids, best corrected visual acuity (BCVA), intraocular pressure (IOP), axial length (AL), anterior chamber depth (ACD) and renal function. Logistic regression methods were used to analyze the risk factors for DR. Results: The prevalence of DR in type 2 diabetes was 28.44%. The duration of diabetes, age, mean arterial pressure (MAP), HbA1c, FBG, urinary albumin/creatinine ratio (UACR), BCVA, AL and ACD were significantly different between the DR and the NDR groups (p＜0.05). Multivariate logistic regression analysis identified age, FBG, UACR and AL as the independent risk factors for DR (OR=0.843, 2.376, 1.049, 0.005; p=0.034, 0.014, 0.016, p＜0.001). Conclusion: Young age, short AL, higher levels of FBG and UACR were the independent risk factors for the progression of DR in type 2 diabetes.